Does Arterio-Venous Fistula Creation Affects Development of Pulmonary Hypertension in Hemodialysis Patients?. (April 2013) - Unal, Aydin; Duran, Mustafa; Tasdemir, Kutay; Oymak, Sema; Sipahioglu, Murat Hayri; Tokgoz, Bulent; Utas, Cengiz; Oymak, Oktay
<x xml:space="preserve">Abstract</x> Background: Pulmonary arterial hypertension (PAH) is a common complication in hemodialysis (HD) patients and its pathogenesis is not explained clearly. Arterio-venous fistulas (AVFs) creation may contribute to the development of PAH because of increased pulmonary artery blood flow. However, it was not prospectively evaluated that effect of AVF on the development of PAH. Aim: We aimed to evaluate the effects of AVF on PAH and the relationship between blood flow rate of AVF and pulmonary artery pressure (PAP) in HD patients. Patients and Method: The prospective study included 50 patients with end-stage renal disease. Before an AVF was surgically created for hemodialysis, the patients were evaluated by echocardiography. Then, an AVF was surgically created in the patients. After mean 76.14 ± 11.37 days, the second evaluation was performed by echocardiography. Results: Before AVF creation, 17 (34%) out of 50 patients had PAH. The systolic PAP was significantly higher in the patients with PAH compared with patients without PAH (47.82 ± 9.82 mmHg vs. 30.15 ± 5.70 mmHg, respectively, p = 0.001). In the second evaluation, 19 (38%) out of 50 patients had PAH. The systolic PAP values were significantly higher in the patients with PAH compared with patients without PAH (47.63 ± 8.92 mmHg vs. 25.03 ± 7.69 mmHg, P = 0.001, respectively). There was no relationship between the blood flow rate of AVF and PAP. Conclusion: PAH is a common problem in HD patients. AVF has no significant effect on the development of PAH within a short period. Similarly, blood flow rate of AVF also did not affect remarkably the systolic PAP.